2003
DOI: 10.1017/s0033291702006980
|View full text |Cite
|
Sign up to set email alerts
|

The economic cost of chronic fatigue and chronic fatigue syndrome in UK primary care

Abstract: Chronic fatigue imposes substantial economic costs on society, mainly in the form of informal care and lost employment. Treatments need to be developed which recognize these impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 21 publications
4
76
0
Order By: Relevance
“…Substantially higher values have been generated using opportunity cost and replacement methods, with values ranging from £3 to £14 per hour, depending on the nature of the task (Nuttall et al, 1993;Laing, 1993;Carers UK, 2002;Buckner and Yeandle, 2007;Schneider et al, 2003;Liu et al, 2002;McCrone et al, 2003). One explanation for this is that the DCE methodology allows for broader aspects of (dis)utility that individuals may derive from the provision of informal care (Van den Berg et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantially higher values have been generated using opportunity cost and replacement methods, with values ranging from £3 to £14 per hour, depending on the nature of the task (Nuttall et al, 1993;Laing, 1993;Carers UK, 2002;Buckner and Yeandle, 2007;Schneider et al, 2003;Liu et al, 2002;McCrone et al, 2003). One explanation for this is that the DCE methodology allows for broader aspects of (dis)utility that individuals may derive from the provision of informal care (Van den Berg et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the lack of a market for such care, questions are raised concerning how such activity can be valued. A number of approaches have been employed, including opportunity cost (Schneider et al, 2003;Liu et al, 2002), market replacement cost (McCrone et al, 2003;Dewey et al, 2002), contingent valuation (CV) (Van den Berg et al, 2005;Van den Berg et al, 2005b) and conjoint analysis (Van den Berg et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…7 Persons with CFS/ME are high users of health care services and more likely than others to be out of work. 8 The diagnosis is surrounded by controversy. 9 Most researchers now accept the view that CFS/ME is multifactorial and distinguish among factors that predispose, precipitate, and perpetuate the condition.…”
Section: Introductionmentioning
confidence: 99%
“…CFS is associated with a high use of health care services and, hence, with high societal costs [2][3][4][5][6]. It has been found that 39% of the CFS population in the UK uses at least one type of prescribed medication and 71% of them receive informal home care [2].…”
Section: Introductionmentioning
confidence: 99%
“…CFS is associated with a high use of health care services and, hence, with high societal costs [2][3][4][5][6]. It has been found that 39% of the CFS population in the UK uses at least one type of prescribed medication and 71% of them receive informal home care [2]. Jones et al [5] found that, compared to nonfatigued controls, more CFS patients reported to using any kind of (un)prescribed medication (92% vs. 82%, Pb.00) and to using more different types of medication (5 vs. 2, Pb.00).…”
Section: Introductionmentioning
confidence: 99%